2018
DOI: 10.3390/su10061827
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on the Ecological Protection Behaviors of Entrepreneurial Farmers in Chinese Forest Zones

Abstract: Abstract:Following the collective forest tenure reforms in China, many households pursued entrepreneurial activities creating substantial pressure on the environment. This study examines data collected from 462 informants in 10 provinces in Southern China to understand how changes in attitudes toward ecological protection behavior occur. The internal mechanisms of ecological attitudes were explored using structural equation modeling to obtain a function path. Ecological emotion has a direct effect on ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Consistent with previous research results, the farmers' cognition was found to significantly affect forest land transfer behavior [51]. However, unlike the findings of Xue et al [52] and Casey et al [53], the study showed that the ecological cognition of all sampled farmers-not just those in specific farmer groups-significantly affected forest land transfer behavior. A possible reason for this is that China's leaders put forward the following important ecological civilization concept: "clear water and green mountains are also gold hills and silver mountains".…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous research results, the farmers' cognition was found to significantly affect forest land transfer behavior [51]. However, unlike the findings of Xue et al [52] and Casey et al [53], the study showed that the ecological cognition of all sampled farmers-not just those in specific farmer groups-significantly affected forest land transfer behavior. A possible reason for this is that China's leaders put forward the following important ecological civilization concept: "clear water and green mountains are also gold hills and silver mountains".…”
Section: Discussionsupporting
confidence: 86%
“…This result is in line with the research by Kollmus and Agyeman [44] where awareness towards the environment leads to green intention and ended in green entrepreneurial behaviour. As stated that green awareness considered not directly impact Green Entrepreneurial Behaviour because in the previous research by Xue et al [45]. Green Awareness needs to be mediated by other variables then it can directly impact.…”
Section: P-value Resultsmentioning
confidence: 88%
“…This result is in line with the research by Kollmus and Agyeman [44] that stated that green awareness needs to be meditated to act then it will lead to behaviour. Green Knowledge considered does not directly affect the green entrepreneurial behaviour based on the previous research that stated that green knowledge needs to be mediated by other variables to reach entrepreneurial behaviour because of its gap between one another [45]. It can be interpreted that how deep the understanding of millennials in Indonesia with the term "green" and knowledge about it, can give a positive direction to the intention of being green entrepreneurs and lead to green entrepreneurial behaviour.…”
Section: P-value Resultsmentioning
confidence: 98%
“…This could be accomplished via market regulation, ecological compensation and ecological protection incentives [39,[41][42][43] and would alleviate environmental damage. More importantly, in fragile ecological areas, an ecological red line should be strictly defined and a new pattern of urban-rural integration should be developed [44][45][46].…”
Section: Discussionmentioning
confidence: 99%